Protein–Protein Interactions in Base Excision Repair - Govardhan Rathnaiah; Joann B. Sweasy (Biomolecules)
The Base Excision Repair (BER) pathway involves a highly coordinated series of protein–protein interactions that facilitate the recognition, excision, and repair of damaged bases. Key enzymes such as DNA glycosylases, apurinic/apyrimidinic endonuclease 1 (APE1), polynucleotide kinase-phosphatase (PNKP), DNA polymerase b (Pol β), ligase IIIα (LigIIIα), poly (ADP-ribose) polymerases PARP1 and PARP2, and X-ray repair cross-complementing protein 1 (XRCC1) catalyze BER in a tightly regulated molecular network. These interactions ensure the seamless handoff of DNA intermediates between the core enzymes of the BER pathway. Understanding the details of protein–protein interactions in BER provides valuable insights into the molecular underpinnings of DNA repair processes. In this review, we focus on protein–protein interactions between the components of the single-nucleotide BER (SN-BER) pathway and other proteins that interact with BER components and regulate the coordination of the pathway. We also briefly discuss the interactions of other proteins that interact with the components of SN-BER based on functional evidence.